2022
DOI: 10.1001/jamaoncol.2022.1628
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Racial and Ethnic Disparities in Patients With Breast Cancer–Related Lymphedema

Abstract: IMPORTANCE Risk factors for breast cancer-related lymphedema (BCRL) after axillary lymph node dissection (ALND) are poorly understood. OBJECTIVE To evaluate rates of and risk factors associated with BCRL in a prospective cohort of women treated with ALND. DESIGN, SETTING, AND PARTICIPANTSThis prospective BCRL screening study performed at a tertiary cancer center enrolled women with breast cancer 18 years and older undergoing breast surgery and unilateral ALND in the primary setting or after sentinel lymph node… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 16 publications
5
29
2
Order By: Relevance
“…Using diagnosis codes to identify cases of lymphedema, Black et al demonstrated that Black patients have higher rates of ALND vs SLNB and higher rates of BCRL following ALND compared with White patients. Our group has similarly shown that Black race and Hispanic ethnicity are independent risk factors for BCRL on multivariable analysis . In this study, we found that the average Black woman treated for breast cancer had a 10.2% risk of lymphedema compared with a 6.9% risk for the average White woman based on our preoperative model, with a similarly significant increase in risk based on our postoperative model.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Using diagnosis codes to identify cases of lymphedema, Black et al demonstrated that Black patients have higher rates of ALND vs SLNB and higher rates of BCRL following ALND compared with White patients. Our group has similarly shown that Black race and Hispanic ethnicity are independent risk factors for BCRL on multivariable analysis . In this study, we found that the average Black woman treated for breast cancer had a 10.2% risk of lymphedema compared with a 6.9% risk for the average White woman based on our preoperative model, with a similarly significant increase in risk based on our postoperative model.…”
Section: Discussionsupporting
confidence: 71%
“…Our model includes any (neoadjuvant or adjuvant) chemotherapy in addition to any radiation therapy, since both have been associated with BCRL risk in prospective cohort studies . Despite strong evidence that neoadjuvant therapy alone is associated with BCRL risk, this variable did not improve the accuracy of our model, potentially due to exclusion bias as neoadjuvant chemotherapy was rarely used during the study period of the 1999 to 2003 MSKCC cohort (data set 1). ALND was the strongest predictor in our preoperative model with a predicted probability of 20.0%, consistent with Level I evidence showing a nearly 4-fold greater risk of lymphedema following ALND vs SLNB .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lymphedema, which can cause limb swelling, discomfort, and impaired arm function, is a major morbidity among breast cancer survivors. The estimated risk of developing lymphedema after treatment is approximately 20% [1][2][3], with the main risk factor being axillary dissection [4,5].…”
Section: Introductionmentioning
confidence: 99%